Physico-chemical properties of collagen extracts from two local fish species - Jaswir, Irwandi; Che Kamaludin, Nur'ain; Mohd. Salleh, Hamzah (IIUM Press, 2011)
Production of high quality gelatin from Labeo rohilO (rohu) skill alld Megalaspis cordyla (torpedo scad) skill and scale as an ahemmive of porcine and bovine gelatin has beell conducted through modificatioll process using transglutaminase. Screening showed that Labeo rohila (rohu) skiJl has a beller quality of gelatiJl with the maximum gel strength and viscosity valucs aftcr the modification. The gel strength is 114.70g with TGase addition while the viscosity is 0.01960 Pa. The resulls of this study suggest that transglutaminase concemration. incubation time alld incubation temperature affect the gel strength and viscosity of the gelatill produced, Central composite Design (CeO) from Design Expert was applied to determille the optimal conditions for the modification for thc highest values of gel strength. The optimum modification conditions were attained at 6·C incubation temperature for 24h incubation time and TGase concentration is 0.1 Sgfml. The gelatin obtained from these conditions is 10.7Ig.